Main leadership style of the agricultural businessmen in the province of Chiclayo, Lambayeque region – Peru - Loli Pineda, Alejandro E. (2021)
Studying leadership styles requires a review of a wide range of literature around the world and for a long time with the intention of understanding the leader's behavior, and there is no doubt that research will continue in the various social, economic and political sectors. The present study aimed to determine the predominant leadership style in a sample of 270 agricultural business man from the province of Chiclayo in Peru, as part of a macro study, promoted by the ONG Association of Farmers La Monteria – ASPAM. The Spanish version of the Multifactor Leadership Questionnaire - MLQ, constructed by Avolio and Bass, was applied; later adapted by Castro Solano, Nader and Casullo in 2004 and called CELID-A (questionnaire of leadership styles-Self-leadership) (Solano, 2018). The results indicate that the predominant leadership style is the transformational style, with low scores for transactional leadership styles and the Laissez-Faire style. It also allowed to know the association and interdependence of transformational, transactional and laissez-faire styles. Furthermore, an analysis of these variables with the socio-demographic data allowed us to find some significant associations.